Level and factors associated with physical activity among university teacher: an exploratory analysis - Katarzyna Kwiecień-Jaguś; Wioletta Mędrzycka-Dąbrowska; Monika Kopeć; Renata Piotrkowska; Katarzyna Czyż-Szypenbejl; Rita Hansdorfer-Korzon; Magdalena Lemska; Piotr Jarzynkowski (BMC, 2021)
Abstract Background Physical inactivity is one of the primary factors that leads to obesity and overweight. What is more, it is becoming an increasingly common problem among the population of those who work. The causes of obesity and the lack of physical activity are multifactorial. The aims of the study were: to (1) measure the level of physical activity among the university staff, (2) evaluate what factors have a significant influence on undertaking the physical activity and lack of. Methods A cross-sectional study was conducted via the Internet questionnaires among university staff in Northern Poland and Pomeranian Region. Taking into consideration the climate and cultural factors in Poland, a physical activity test with the usage of IPAQ scale was performed between September and November 2018 and between March and June 2019. The data was collected on the basis of the standardized long form of the IPQA questionnaire, the GSE Scale and the interview questionnaire including questions about sex, age and health assessment. Results The study group consisted of 276 respondents, including 143 women (51.8%) and 133 men (48.2%). The average age of the respondents was 42.22 with SD ± 11.01. The weight status was categorized with the use of BMI index. 51.3% (142) of the respondents had normal body mass, 93 (33.8%) were overweight, while 23 (8.4%) were obese. The mean BMI index was 25.23 points (SD ± 4.04). One hundred and twenty five (45.1%) respondents were the employees of the Medical University, and 54.9% were employed by the Technical University. Detailed analyses using Spearman correlation test confirmed the presence of a statistically higher level of physical activity among respondents employed at the Medical University (M 513.37; SD ± 609.13) than the employees of Technical University (M 378.38; SD ± 328.26). The odds ratio analysis shows that a low level of physical activity in the group of technical university staff has a significant correlation with the other social behavior which is the alcohol consumption. Conclusion This study confirms that the number of points obtained in the IPAQ scale, classified the academics in the workgroup presenting low physical activity which does not exceed 600 MET-min/week. The most common form of activity in this group was walking. There was no correlation between physical activity and self-efficacy, age, marital status or the number of children.